Laparoscopic ureterolithotomy: a rare case report - Ravi, Dinesh Kumar; Jain, Udit; Dayapule, Sreedhar; Praveen, Guru; Shaikh, Jamal (International Journal of Research in Medical Sciences, 2024)
In this era of endourology most of the ureteric calculi are managed by endourological technique. However, lap ureterolithotomy has a role in the management of large ureteric calculus with minimal complications, morbidity, early recovery and short hospital stay. Laparoscopic ureterolithotomy bridges the gap between open and endourologic procedures as it is minimally invasive and overcomes a few of the disadvantages of open ureterolithotomy. We report a case of our experience of impacted upper ureteric calculus done by laparoscopy. Here we present a case of 45 -year-old male with right loin pain with CT suggestive of impacted right upper ureteric calculus measuring 2.2×1×2.2 with moderate HDUN and good renal function. Patient underwent right transperitoneal laparoscopic ureterolithotomy and, the ureteric calculi was removed successfully. Hence, we can conclude that, laparoscopic uretrolithotomy is safe for large impacted ureteric calculus with early recovery and minimal morbidity to the patient with complete clearance.